Comparison of ultrasonography, electromyography, and clinical findings of patients with carpal tunnel syndrome - Kaya, Oğuz; Gürbüz, Ali; Batur, Ömer Cihan; Taş, Nevsun Pıhtılı; Yıldırım, Mustafa; Senel, Ahmet (My University, 2023)
In the present study, we compared ultrasonography (USG), electromyography (EMG), and clinical outcomes of patients exhibiting clinical findings suspected of carpal tunnel syndrome (CTS). This comparison included individuals diagnosed with CTS through control examinations involving electrodiagnostic tests, as well as those who were not diagnosed with CTS. The study included 50 patients who applied to the Physical Medicine and Rehabilitation and Orthopedics and Trauma- tology outpatient clinics at Elazig Fethi Sekin City Hospital with complaints of hand numbness and pain, raising suspicion of CTS and were subsequently diagnosed with CTS through EMG between January 2022 and June 2022. In addition, the records of 50 control patients were reviewed; these individuals were also suspected of CTS and had undergone EMG, but their results were determined to be normal upon interpretation. All patients completed the Boston CTS questionnaire, while a radiologist with seven years of experience employed a linear probe within a 5-13 MHz frequency range to measure and record the cross-sectional area (CSA) of the wrist median nerve. The patient group comprised the evaluation of 87 wrists, whereas the control group included 79 wrists under assessment. The mean age for the patient group stood at 49.94±8.9 years, while the control group exhibited a mean age of 51.61±9 years. There was a significant correlation between the median nerve CSA measured by USG and the corresponding EMG data. In our study, we concluded that both EMG and USG are effective in the diagnosis of CTS, with USG exhibiting greater effectiveness compared to EMG.
Keywords: Ultrasonography; electromyography; carpal tunnel syndrome; Boston CTS questionnaire